Tell me your names and I will testify - Holbrook, Carolyn (Carolyn L.) (University of Minnesota, 2020)
"Recipient of the 2010 Kay Sexton Award, Tell Me Your Names and I Will Testify are the long-awaited collection from local literary figure Carolyn Holbrook. A collection of linked essays, Tell Me Your Names follow Holbrook's transformation from a pregnant 16-year-old incarcerated in the Minnesota juvenile justice system through her years living in Minneapolis, raising a family, and eventually to the founder of an organization that challenges conventional ideas about writers of color and provides support for them. Each essay grows from, in some way, stories that are born from silence, or being silenced; stories held inside and untold, hidden traumas: from her family history; her time incarcerated as a teen mother; her life as a teacher, especially working with children of color; cycles of domestic and sexual abuse; and why telling these stories is so necessary for working through traumas personal and collective"--